Analisis Kinerja Dinas Pemberdayaan Masyarakat Dan Desa (Dpmd) Dalam Proses Penyaluran Bantuan Langsung Tunai Dana Desa (Blt-Dd) Kepada Pemerintah Desa - Rafit Yusriandi; Nodi Marefanda (JIAP (Jurnal Ilmu Administrasi Publik), 2023)
This study aims to analyze the performance of employees of the community and village empowerment offices of Simeulue Regency in distributing direct cash assistance for village funds (BLT-DD). The method used in this research is descriptive qualitative with the acquisition of data sources through observation methods, interviews, and documentation. The results of the research obtained based on aspects  of productivity, service quality, responsiveness, responsibility, and accountability, show that the performance of the Community and Village Empowerment Office in Distributing Village Fund Cash Direct Assistance to Village Governments in Simeulue Regency shows  maximum results. . This is based on the five aspects of standards that are indicators of the performance of government agencies that can be fully met. Although there are still some things that need to be addressed. However, overall, the performance of the Simeulue Regency Community and Village Empowerment Office (DPMD) can be said to be optimal.